Projeto consciência corporal: alívio das tensões e interiorização pessoal - Ribeiro, Fernanda Elisa [UNESP]; Palma, Mariana Romanholi [UNESP]; Teixeira, Larissa Ruiz [UNESP]; Araújo, Mariane Fátima da Silva [UNESP]; Mantovani, Alessandra Madia [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Mind-body therapies are considered low intensity modalities that comprise health in the physical and mental aspect. The Body Awareness Therapy (CBT) is also based on this principle and aims to restore balance between mind and body and thus promote health benefits. Given the positive effects that TCC has provided health, the University Extension Project "Project body awareness: easing of tensions and personal internalization", the Faculdade de Ciências e Tecnologia (FCT) da Universidade Estadual Paulista (UNESP) of Presidente Prudente, allows participants into contact with this treatment modality. Objective: To determine the physical and emotional profile of participants in the University Extension Project "Project body awareness: easing of tensions and personal internalization" of the FCT / UNESP, in order to verify in the future, the potential benefits generated after an intervention period. Methods: Participants are individuals interested in increasing your body awareness through the practice of TCC (women who underwent surgery for breast cancer, individuals with musculoskeletal diseases, as well as people with no detected pathologies). To analyze the physical profile, we evaluated body mass index (BMI), lateral trunk flexibility and posterior chain (Wells bank). To the emotional profile were evaluated symptoms of stress (Inventário de Sintomas de Stress de Lipp - ISSL), anxiety and depression (Hospital Anxiety and Depression Scale - HADS). Results: Became evident that the participants (n = 14), mean age 39.14 ± 17.11 years, are overweight (BMI 25.05 ± 4.37 kg / m²), lateral flexibility right trunk (18.17 ± 5.82 cm) and left (18.50 ± 5.10 cm) similars, little posterior chain flexibility (24.43 ± 10.36 cm), stress symptoms (resistance phase and 57.14% exhaustion phase 7.14%), anxiety (57.14%) and depression (21.43%). Conclusion: The variables investigated about the physical and emotional profile suggests attention to the health status of participants, as were verified overweight condition, limited flexibility, high levels of stress and anxiety and considerable level of depression.

Terapias mente-corpo são consideradas modalidades de baixa intensidade que compreendem a saúde no aspecto físico e mental. A Terapia de Consciência Corporal (TCC) também se baseia neste princípio e tem como propósito restabelecer equilíbrio entre mente e corpo e, assim, promover benefícios à saúde. Perante aos efeitos positivos que a TCC tem propiciado à saúde, o Projeto de Extensão Universitária “Projeto consciência corporal: alívio das tensões e interiorização pessoal”, da Faculdade de Ciências e Tecnologia (FCT) da Universidade Estadual Paulista (UNESP) de Presidente Prudente, permite aos participantes o contato com esta modalidade terapêutica. Objetivo: Verificar o perfil físico e emocional dos participantes de um Projeto de Extensão Universitária da FCT/UNESP, a fim de verificar, futuramente, os possíveis benefícios gerados após um período de intervenção. Métodos: Participam indivíduos com interesse em aumentar sua percepção corporal por meio da prática da TCC (mulheres que realizaram cirurgia por de câncer de mama, indivíduos com patologias musculoesqueléticas, bem como pessoas sem patologias detectadas). Para análise do perfil físico, avaliou-se índice de massa corporal (IMC), flexibilidade lateral de tronco e de cadeia posterior (banco de Wells). Para o perfil emocional, foram avaliados sintomas de estresse (Inventário de Sintomas de Stress de Lipp – ISSL), ansiedade e depressão (Hospital Anxiety and Depression Scale - HADS). Resultados: Evidenciou-se que as participantes (n=14), com idade média de 39,14±17,11 anos, apresentam sobrepeso (IMC 25,05±4,37 kg/m²), flexibilidade lateral de tronco direita (18,17±5,82 cm) e esquerda (18,50±5,10 cm) similares, pouca flexibilidade de cadeia posterior (24,43±10,36 cm), sintomas de estresse (fase de resistência 57,14% e fase de exaustão 7,14%), ansiedade (57,14%) e depressão (21,43%). Conclusão: As variáveis investigadas a respeito do perfil físico e emocional sugerem atenção ao estado de saúde das participantes, visto que foram verificados condição de sobrepeso, limitada flexibilidade, elevados níveis de estresse e ansiedade e considerável estado de depressão.
Keywords: Health; Mind-body therapies; Stress; Estresse; Saúde; Terapias mente-corpo